Starea de spirit a populației pe parcursul tranziției. Un model de periodizare - Precupețu, Iuliana (Calitatea Vieții, 2010)
This article describes the subjective well being in Romania during transition. The trajectories of indicators like life satisfaction, happiness, optimism and concerns are followed in time and in relation to the general dynamic of society. Using data from a national survey as well as invoking Eurobarometer data, the paper identifies several distinct periods in the dynamic of subjective well being. The first two years of post communist transformation, 1990–1991 have been described as “the start of great expectations” while the following period of four years was considered as a “period of survival and adaptation endeavours” from the part of population. Up to year 2000, it followed a period of “deceived hopes” as the high expectations of the early 90’s coupled with the high social costs supported by population did not lead to the expected outcome of a wealthier and happier society. Only after year 2000 we can discuss of a “period of impetus and higher well being”.